Analysis of chemical fertilizer application efficiency by cotton farmers and its influence factors an empirical study based on peasant household survey in Shache County - Yan Lu; Ma Huilan (浙江大学学报. 农业与生命科学版, 2014)
Chemical fertilizer application efficiency is an important influence factor in agricultural production. Low chemical fertilizer application efficiency not only lead to cotton production cost increase and constrain cotton per unit area yield, but also may cause agricultural non-point source pollution, because excessive use of chemical fertilizers damage inevitably the environment and resources which are vital for agricultural development. Therefore, our aim is first to systematically evaluate chemical fertilizer application efficiency by cotton farmers. And second, with the purpose to figure out the essential ways to raise production efficiency of agricultural internal system, we assess the active results of different kinds of influence factors of technical efficiency. Furthermore, we hope the results can help to increase agricultural economic benefits of farmers and agricultural scientific and technical level, and ultimately prompt the sustainable development of agriculture.By using the field survey data which were obtained from 203 peasant households in Shache County, a first agricultural county in Xinjiang with favorable cotton plant conditions, an evaluation model with stochastic frontier approach (SFA) was constructed to analyze the chemical fertilizer application efficiency by cotton farmers and then tried to estimate cotton production technical efficiency and chemical fertilizer application efficiency of different groups of cotton farmers to some extent. After that, a double logarithmic model, built by SPSS 17.0 statistical software, was used to assess the relationship between chemical fertilizer application efficiency and thirteen influence factors, and further to find the major reason why the chemical fertilizer application efficiency in Shache County's cotton production was rather lower.The result showed that the chemical fertilizer application efficiency in cotton production of Shache County was merely 0.459 8, which was much lower than appropriate result, indicating that, under the current technical stage, only a small amount of chemical fertilizers used was absorbed by cotton plants. To be more specific, the more obvious influence factor for chemical fertilizer application efficiency was farmers' education level, followed by farmers' perception to chemical fertilizer utilization rate, agricultural technology training, and soil quality change, the proportion of farmers who carry out agricultural production and the application of organic fertilizers. While on the other side, the factors which had lower influence on chemical fertilizer application efficiency were plant scale, chemical fertilizer price change and working hours on farmland. Another point which was worthy mentioning was that only the soil quality change had negative influence on chemical fertilizer application efficiency.In the end, on the basis of empirical analysis in the study, a number of counter-measures (e. g. improving farmers' educational level, enforcing agricultural technology extension, prompting agricultural production and operation in moderate scale and controlling chemical fertilizer price) were proposed to increase the chemical fertilizer application efficiency and reduce the possibility of agriculture non-point pollution.